P800 Factors related to non-adherence behaviours of patients with inflammatory bowel disease. (25th January 2019) - Marín-Jiménez, I; Casellas, F; García-Sepulcre, M F; Navarro-Correal, E; Juliá, B; Soto, N; Cea-Calvo, L
Abstract: Background: Non-adherence to medication leads to poorer outcomes and must be prevented. We describe the frequency of non-adherence behaviours in patients with inflammatory bowel disease (IBD) and its relationship to potentially modifiable variables. Methods: Data were obtained through an anonymous survey. Five different non-adherence behaviours were defined, and co-variables analysed were patients' demographics, experience with healthcare (assessed with IEXPAC 'Instrument to Evaluate the EXperience of PAtients with Chronic diseases' scoring 0 [worst] to 10 [best experience]), beliefs in medicines (Beliefs About Medicines Questionnaire [BMQ], composed of a necessity and a concerns scale and scoring −20 [weaker] to +20 [stronger beliefs]) and medication characteristics. Variables associated to nonadherence were studied with a multi-variate logistic regression model. Results: Overall, 332 of 575 IBD patients (58%) returned the survey with the necessary data completed (mean age 47 [13] years, 48% women), of which 179 (56%) had at least one non-adherence behaviour. The frequency of the specific non-adherence behaviours was: (1) Forgiveness in taking medication: 36%; (2) Taking medication at unscheduled hours: 6%; (3) Leaving medication when feeling well: 10%; Leaving medication when feeling sick: 28% and 5) Stopping medication after reading the patients' information leaflet: 8%. The frequency of at least one non-adherence behaviour was similar by age, gender, educational level, working status, number of medicines taken or doses per day needed. Non-adherence behaviours were more frequent in patients with lower (worse experience) IEXPAC scores (Quartile [Q] 1: 64%, Q2: 62%, Q3: 44%, Q4: 47%, p-trend: 0.005) or lower (low-necessity / high concerns) BMQ score (Q1: 65%, Q2: 61%, Q3: 52%, Q4: 39%, p -trend < 0.001). The multi-variate model (table) confirmed the relationship of non-adherence behaviours with worse experience and lower BMQ beliefs scores. Multi-variate analysis. Factors associated to non-adherence behaviours of IBD patients Conclusions: Non-adherence behaviours are frequent in IBD patients and are mainly associated to two aspects with potential to be addressed in daily clinical practice to prevent non-adherence: their experience with healthcare (measured with IEXPAC) and their beliefs in medications (assessed with BMQ). The study was funded by Merck Sharp & Dohme of Spain and endorsed by 4 patients associations (ACCU: patients with Crohn's disease and ulcerative colitis; CONARTRITIS: patients with arthritis; SEISIDA: AIDS multi-discipline group, FEDE: patients with diabetes mellitus).